2004
DOI: 10.4269/ajtmh.2004.71.222
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Eosinophilic Meningitis Associated With Drinking Raw Vegetable Juice in Southern Taiwan

Abstract: The most common cause of eosinophilic meningitis is the rat lungworm Angiostrongylus cantonensis a parasite that is endemic in the southeast Asian and Pacific regions. Outbreaks of eosinophilic meningitis associated with drinking raw vegetable juice are rarely reported, even in regions of endemic infection. We performed a cohort study among Taiwanese with eosinophilic meningitis who drank raw vegetable juice within three months of the onset of the outbreak. Clinical manifestations, laboratory examinations, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 17 publications
0
66
0
1
Order By: Relevance
“…Other studies have reported infection from consuming undetected small slugs, snails, or planaria on produce (e.g., in a Caesar salad and raw vegetable juice). 5,10,11,28,34 Although we did not identify a point source for this outbreak, unintentional consumption of snails/slugs or larvae in homegrown produce likely occurred on the island of Hawaii; almost all case-patients there described consuming produce from their own (or a non-commercial) garden, usually unwashed. Environmental studies found A. cantonensis larvae in slugs in the yards of the infant with a parasitologically confirmed case and two case-patients who shared a household.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Other studies have reported infection from consuming undetected small slugs, snails, or planaria on produce (e.g., in a Caesar salad and raw vegetable juice). 5,10,11,28,34 Although we did not identify a point source for this outbreak, unintentional consumption of snails/slugs or larvae in homegrown produce likely occurred on the island of Hawaii; almost all case-patients there described consuming produce from their own (or a non-commercial) garden, usually unwashed. Environmental studies found A. cantonensis larvae in slugs in the yards of the infant with a parasitologically confirmed case and two case-patients who shared a household.…”
Section: Discussionmentioning
confidence: 87%
“…There have been few studies of potential sources of accidental or incidental exposure; presumptive transmission from food items contaminated with larvae (e.g., salad or juice containing snails, slugs, or larvae) has been reported. 5,10,11 After penetrating the gastrointestinal tract, the larvae spread hematogenously to the central nervous system. 12,13 Following an average incubation period of 1-3 weeks, symptomatic persons often develop headache, meningeal symptoms, and sensory abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Another source of infection can be other mollusks, and paratenic hosts, such as frogs, freshwater prawns, crabs, fish, and planaria. A less common path of infection is ingestion of contaminated vegetables, water, or fruit juice (262,280). Hands may carry the larvae directly to the mouth, after manipulation of or playing with mollusks, which is likely the main mode of infection among young children.…”
Section: Epidemiologymentioning
confidence: 99%
“…There was usually a history of eating or playing with snails or slugs. Only three scattered outbreaks were found to have occurred during the past two decades caused by eating raw golden apple snails and drinking raw vegetable juice (10,11). Frogs and toads are known as paratenic hosts of A. cantonensis (12).…”
Section: Introductionmentioning
confidence: 99%